The Effect of Parental Attention and Learning Motivation on Students’ Mathematics Learning Achievement - Ahmad Nizar Rangkuti (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Various external and internal factors influence student achievement. This study aimed to determine the effect of parental attention and learning motivation on students’ mathematics learning achievement both partially and simultaneously. This research is quantitative research with an ex-post-facto approach. The population of this study was 260 eleventh-grade students in one of the Islamic senior high schools in Mandailing Natal, North Sumatera. The sample was 60 students chosen by cluster sampling. The data on parental attention and student learning motivation were collected using questionnaires and documentation, while data analysis was using the regression analysis method. The results showed that there was a significant effect of parental attention and learning motivation on students' mathematics learning achievement partially and simultaneously. Therefore, parents need to pay attention to their children's learning needs and control their activities outside school to improve student learning achievement. In addition, teachers need to apply suitable learning methods to increase student motivation.